Bioaccumulation of contaminants in wild seahorses collected from coastal China - Liu, Ying; Shang, Dongwei; Yang, Yanjing; Cui, Pei; Sun, Jinhui (Frontiers in Marine Science, 2022)
Eighty-four wild seahorses, including three of China’s dominant species, were collected from seven coastal provinces to evaluate their common contaminant contents. Heavy metals (including Cu, Pb, Cd, Cr, and Hg), Benzo(a)pyrene (B[a]P), and microplastics were detected in the collected seahorses. The results indicate that considerable contamination variations are present in seahorses from different regions and species. Elevated concentrations of Cu and Cr, compared to other heavy metals, were observed in most sampled locations. In addition, B[a]P concentrations were far greater in Hippocampus mohnikei and H.trimaculatus compared with H.kelloggi (P < 0.05). Substantial changes in microplastic concentrations were also observed in seahorses from different locations, and significant differences were observed between sampled species (P < 0.05). Further, a correlation analysis obtained strong correlations among four heavy metals (Cu, Pb, Cd, and Cr), except Hg. A significant correlation was identified between B[a]P and microplastics (P < 0.01), suggesting potential synergistic effects between these two contaminants. In brief, this study indicates that wild seahorse populations are experiencing environmental pollution.